Medicine, State and Reproduction in Brazil at the beginnings of the twentieth century - Rohden, Fabiola (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2007)
This article shows that medical specialties involving women, reproduction, and sexuality -specialties that gained relevancy in the initial decades of the 20th century- are linked to the production of eugenicist and nationalist politics in Brazil. It analyzes scientific production in the fields of gynecology, obstetrics, and childcare, as presented in academic theses and medical journals between 1900 and 1940. This material both shows how ideas concerning the need to increase the birthrate, expressed most tellingly in the valorization of motherhood, are constructed, and also how the birth of individuals who are considered undesirable was restricted through sterilization and other contraceptive practices.